Vertically and horizontally directed muscle power exercises: Relationships with top-level sprint performance - Loturco, I.; Contreras, B.; Kobal, R.; Fernandes, V.; Moura, N.; Siqueira, F.; Winckler, C.; Suchomel, T.; Pereira, L. A. (PLOS ONE, 2018)
The capacity to rapidly generate and apply a great amount of force seems to play a key role in sprint running. However, it has recently been shown that, for sprinters, the technical ability to effectively orient the force onto the ground is more important than its total amount. The force-vector theory has been proposed to guide coaches in selecting the most adequate exercises to comprehensively develop the neuromechanical qualities related to the distinct phases of sprinting. This study aimed to compare the relationships between vertically-directed (loaded and unloaded vertical jumps, and half-squat) and horizontally-directed (hip-thrust) exercises and the sprint performance of top-level track and field athletes. Sixteen sprinters and jumpers (including three Olympic athletes) executed vertical jumps, loaded jump squats and hip-thrusts, and sprinting speed tests at 10-, 20-, 40-, 60-, 100-, and 150-m. Results indicated that the hip-thrust is more associated with the maximum acceleration phase (i.e., from zero to 10-m; r = 0.93), whereas the loaded and unloaded vertical jumps seem to be more related to top-speed phases (i.e., distances superior to 40-m; r varying from 0.88 to 0.96). These findings reinforce the mechanical concepts supporting the force-vector theory, and provide coaches and sport scientists with valuable information about the potential use and benefits of using vertically- or horizontally-based training exercises.